EFFECT OF DYNAMIC IMPACTS OF TRANSPORT RENOVATED BUILDINGS - and (Municipal economy of cities (Technical science), 2013)
The parameters of dynamic effects from transport and causes, increasing their negative influence on exploiting buildings, are analyzed. The example of modeling of the dynamic effects on building, located near-by transport highways, and results of numeral researches of their vibrations at the different models of co-operating of building with foundation under dynamic influences with finite elements method are shown. The analysis of dependences of dynamic parameters of building from the method of modeling of co-operating of buildings with their foundations is presented.